Minor (Under-utilized) Fruits in Coochbehar District of West Bengal, India– an Analysis on Marketing Status for Economic Viability - Roy, Tuhin Narayan (International Journal of Bio-resource and Stress Management, 2014)
This paper is analytical in nature and presents the findings of a study carried out on primary information/data collected Coochbehar district of West Bengal during 2010-11 on marketing of minor (under-utilized) fruits in order to find out the status of marketing and to suggest suitable marketing strategies for viable economic proposition. Major fruits are cultivated in most tropical (and subtropical) countries for both local and international markets. Minor fruits have limited cultivation, consumption and trade. Coochbehar district of West contributes about 33% major and minor fruits. Marketing remains a big problem for these fruits qualitatively and quantitatively. Most of the minor fruits are season-bound, scattered in distribution, marketed in fresh form but marketed surplus is insignificant, though the market prices are high in absence of definite channels (supply chain), set pattern of pricing and prescribed standards for grading. High risk factors and investment costs discourage the private entrepreneurs for investment. Some constraints of marketing are lack of reliable statistical data, consumers’ ignorance, long gestation period, mode of storage and ripening and absence of post harvest operations (processing). Generation of awareness about economic, nutritional and environmental values, identification of potential minor fruits, adoption of improved cultivation and appropriate post-harvest technology, provision of standardization of production technology, mobilization/formation of local entrepreneurs, analysis of buyers’ and sellers’ perceptions and behaviours, govt. policy to support a source of income as well as minor fruits cultivation are some of the recommendations.